2013
DOI: 10.3109/09546634.2013.806979
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of the 595 nm pulsed dye laser in the treatment of childhood superficial hemangioma – analysis of 10-year application in Chinese patients

Abstract: Our experience confirmed the satisfactory clinical efficacy and safety of the 595 nm tunable pulse dye laser in the treatment of childhood superficial hemangioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…But there is controversy about the role of PDL in the treatment of IH. We found that the 595 nm PDL can improve treatment efficiency in patients with superficial hemangiomas, with fewer side-effects [8]. 595 nm PDL has been used in our department for the treatment of skin vascular disease, mainly for IH and port wine stains, since 2005.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…But there is controversy about the role of PDL in the treatment of IH. We found that the 595 nm PDL can improve treatment efficiency in patients with superficial hemangiomas, with fewer side-effects [8]. 595 nm PDL has been used in our department for the treatment of skin vascular disease, mainly for IH and port wine stains, since 2005.…”
Section: Discussionmentioning
confidence: 85%
“…Michel [10] and Witman et al [11] reported that the majority of hemangiomas had different side-effects after PDL treatment but these side-effects could be tolerated in our limited databases [8]. Many documents have reported side-effects arising in patients with hemangioma treated by PDL.…”
Section: Discussionmentioning
confidence: 93%
“…). Among 153 publications included in the full review, 29 studies addressed lasers: 12 comparative studies (4 RCTs, reported in multiple publications, of good and fair quality and 8 retrospective cohort studies of fair and poor quality ) and 17 case series (1 good , 2 fair , and 14 poor quality for harms reporting ). Most studies included children with IH in multiple locations; one included children with only airway IH and another with hand IH .…”
Section: Resultsmentioning
confidence: 99%
“…Two cohort studies compared PDL with adjunctive β‐blockers and with β‐blockers alone . Case series reported harms associated with PDL , Nd:YAG lasers , combined PDL and Nd:YAG , long‐pulse Alexandrite laser , and CO 2 laser . Table outlines key study outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…As the leading effective laser treatment for IH, PDL works through selective photothermolysis to prevent enlargement and promote involution of IH [25,26]. Instead of waiting passively for natural regression that may take a long time and even lead to suboptimal cosmetic results and psychosocial distress despite later intervention, the high safety profile of topical timolol and/or PDL presents a splendid opportunity to actively intervene early, safely, and nonsystemically with a higher likelihood of earlier and complete regression [10,12,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%